Assessing the impact of a 'bundle of care' approach to Staphylococcus aureus bacteraemia in a tertiary hospital. Issue 4 (December 2020) - Green, Jared; Howard, Julia; Shankar, Avinesh; Clinghan, Richard; Luff, Tessa; Birch, Mark; Pithie, Alan; Werno, Anja; Metcalf, Sarah; Chambers, Stephen
Summary: Background: Staphylococcus aureus bacteraemia is associated with significant morbidity and mortality. There is evidence that standardised care bundle implementation may improve the rates of appropriate investigations and improve overall management. A S. aureus bacteraemia care bundle was introduced at Christchurch Hospital, New Zealand in early 2014. We assessed the impact of the intervention on the management and outcome of S. aureus bacteraemia. Methods: A cohort study of cases of S. aureus bacteraemia was conducted following standardised care bundle introduction. Prospective enrolment of post-intervention patients occurred from 1 st January 2014 to 30 th June 2015, with retrospective review of pre-intervention cases from 1 st January 2009 to 31 st December 2013. Results: In the pre-intervention period 447 patients had at least one episode of S. aureus bacteraemia compared to 151 patients in the post-intervention period. The two groups were similar by gender, ethnicity, and age. Significant increases in Infectious Diseases consultation rate (86.6% vs 94.8%; p=0.009), echocardiography (76.3% vs 96.3%; p<0.001), urine culture (74.0% vs 91.9%; p<0.001), follow up blood cultures (44.2% vs 83.0%; p<0.001), and at least 2 weeks of parenteral therapy (83.5% vs 92.9%; p=0.014) were observed after introduction of the bundle. There were no significant differences in rates 30-day mortality (18.6% vs. 20.5%; p=0.596), but there was a reduction in episodes of relapsed infection in the post-intervention cohort (7.4% vs 1.3%; p=0.004). Conclusion: An integrated care bundle for the management of S. aureus bacteraemia resulted in increased use of quality of care indicators and infectious diseases review and improved patient outcome.